1992
DOI: 10.1161/01.hyp.19.6.676
|View full text |Cite
|
Sign up to set email alerts
|

Captopril prevents chronic hypertension produced by infusion of endothelin-1 in rats.

Abstract: Endothelin-1 (ET-1), a potent vasoconstrictor peptide synthesized by the vascular smooth muscle endothelium, has been previously shown to produce a sustained, salt-sensitive elevation in mean arterial pressure when chronically infused over a 7-day period into male Sprague-Dawley rats. In addition to other physiological actions, ET-1 has been shown to have potent effects on various renal functions, including renin production. Activation of the renin-angiotensin system, therefore, may contribute to the pressor r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

1994
1994
2006
2006

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Although some studies have shown that ET infusion in rats causes elevation of blood pressure [82], other studies have demonstrated that ET infusion causes slight or no change [56]. The difference in the results could be related to the activity of the ET batches from different commercial sources.…”
Section: Vascular Et and Other Control Mechanisms Of Blood Pressurementioning
confidence: 90%
“…Although some studies have shown that ET infusion in rats causes elevation of blood pressure [82], other studies have demonstrated that ET infusion causes slight or no change [56]. The difference in the results could be related to the activity of the ET batches from different commercial sources.…”
Section: Vascular Et and Other Control Mechanisms Of Blood Pressurementioning
confidence: 90%
“…The action of endothelin (ET), a potent vasoconstrictor of endothelial origin, 911 was used to test this hypothesis. Although the systemic infusion of ET can produce hypertension in the rat, 12 a controversy exists as to whether the circulating levels of this factor are increased in essential hypertension. Moreover, it is uncertain whether elevated levels of ET cause hypertension in humans (reviewed in Reference 7).…”
Section: Endothelin Mobilizes Calcium and Enhances Glucose Uptake In mentioning
confidence: 99%
“…43 -44 Several observations support the idea that the special relation between ET and Ang II plays an important function in the pathophysiology of essential hypertension. First, the ACE inhibitor captopril prevents chronic hypertension produced by the systemic administration of ET in the rat 12 ; second, captopril improves the impaired endothelium-dependent vasodilation in patients with essential hypertension 45 ; and third, Ang II stimulates ET production and augments the contractility of resistance vessels of the spontaneously hypertensive rat to a greater extent than the Wistar-Kyoto rat. 40 Taken together, these observations suggest that at least some forms of essential hypertension are marked by hyperactivity of ET and Ang II or increased sensitivity to these agents of the peripheral circulation.…”
mentioning
confidence: 99%
“…In addition, treatment with an angiotensin converting enzyme (ACE) inhibitor attenuated the reductions in renal blood flow and urinary sodium excretion induced by acute administration of ET-1 (11). Similarly, the hypertension induced by chronic infusion of ET-1 was prevented by an ACE inhibitor (12).…”
Section: Introductionmentioning
confidence: 99%